Improving the success of simulation projects using 3D visualization and virtual reality. Issue 12 (1st December 2020) - Akpan, Ikpe Justice; Shanker, Murali; Razavi, Rouzbeh
Abstract: Achieving success in computer simulation projects has been a long-standing challenge. A recent study identifies 193 success statements (SSs) distributed across 5 critical success factors (CSFs) and 15 key performance indicators (KPIs) for evaluating simulation projects. This article employs text analytics and sentiments analysis to evaluate the effectiveness of two-dimensional (2D) display and three-dimensional visualization/virtual reality (3D/VR) on the success of a simulation project. The study matches the sentiments from the literature selected through a systematic review process against the SSs, CSFs, and KPIs. The results establish that visual display can influence simulation projects in four ways. First, the combined visualization techniques in 2D and 3D/VR affect nearly half of the SSs across all the CSFs and KPIs, indicating an essential contribution to the success of simulation projects. Second, the 3D/VR is significantly more potent and influences more SSs across all the KPIs and CSFs compared to the 2D display. Third, the 2D display affects fewer but vital SSs, CSFs, and KPIs, especially those related to the time-sensitivity of project delivery, offering a logical explanation to the continued use of 2D visualization by simulation providers. Fourth, ensuring success in a computer simulation project requires multifaceted evaluation criteria.